THE GIG ECONOMY: OPPORTUNITIES AND CHALLENGES FOR WORKERS AND BUSINESSES - Iskandarov Sunnatillo Baxriddin o‘g‘li; Abdusattarov Dilshod Axmad oʻg‘li (Academia One, 2024)
The gig economy has emerged as a prominent employment model, offering both opportunities and challenges for workers and businesses alike. This article explores the dynamics of the gig economy, examining the benefits and drawbacks for workers seeking flexibility and businesses looking for on-demand talent. Through an analysis of current trends, regulatory issues, and technological advancements, it highlights the diverse range of opportunities available in the gig economy, from ride-sharing and food delivery to freelance work and task-based projects. Additionally, it addresses the challenges faced by gig workers, including job insecurity, lack of benefits, and income volatility, as well as the implications for businesses in terms of workforce management, liability, and reputation management. By understanding the complexities of the gig economy and adopting strategies to mitigate risks and maximize opportunities, both workers and businesses can navigate this evolving landscape and thrive in the digital age
Keywords: gig economy; freelancing; on-demand work